2010
DOI: 10.1016/j.ijid.2010.02.1749
|View full text |Cite
|
Sign up to set email alerts
|

Mycotic keratitis in Mashhad, Iran: Predisposing factors, etiologic agents & clinical manifestation

Abstract: e119 was 1-4 g/ml for pentamycin, 1-2 g/ml for nystatin, 0.5-1 g/ml for amphotericin B and 1-32 g/ml for fluconazole. Some strains of C. glabrata and S. cerevisiae, and most strains of C. krusei were categorized as susceptible-dose dependent or resistant to fluconazole, according to the CLSI document (MIC > 8 g/ml). At concentrations)4 g/ml, pentamycin inhibited completely the growth of 100% of strains of all species tested, including those strains less susceptible to fluconazole (MIC range: 16-32 g/ml). Concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A study by Sujatha et al also indicated that fungal infection in DFU was higher among males than females; however, the association was also insignificant (p > 0.05) [10]. Another study by Raza and Anurshetru, 2017 and Fata et al, conducted on 100 and 120, repetitively, cases of diabetic foot ulcers demonstrated a high incidence of infection in males (71%) and (71.6%) than females (29%) and (28.4%) with significant p < 0.05 [4], [11].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Sujatha et al also indicated that fungal infection in DFU was higher among males than females; however, the association was also insignificant (p > 0.05) [10]. Another study by Raza and Anurshetru, 2017 and Fata et al, conducted on 100 and 120, repetitively, cases of diabetic foot ulcers demonstrated a high incidence of infection in males (71%) and (71.6%) than females (29%) and (28.4%) with significant p < 0.05 [4], [11].…”
Section: Discussionmentioning
confidence: 99%